Photosynthetic carbon fixation by tropical coral reef phytoplankton assemblages: a UVR perspective - Li, Gang; Che, Zhiwei; Gao, Kunshan; 高坤山 (KOREAN SOC PHYCOLOGY, 2013)
National Natural Science Foundation [40930846, 41120164007, 41206132]; National Basic Research Program of China [2009CB421207]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; China-Japan collaboration project from MOST [S2012GR0290]; Guangdong Natural Science Foundation [S2011040000151]; MEL Visiting Fellowship Program [MELRS1006] Photosynthetic carbon fixation regulates air-sea CO2 fluxes in the waters of coral reefs. However, little has been documented on the effects of solar UV radiation (UVR, 280-400 nm) upon photosynthetic behaviors of phytoplankton dwelling in these ecosystems. In order to evaluate the aforesaid, surface dwelling tropical coral reef phytoplankton assemblages collected from the South China Sea were exposed to solar radiation (i.e., photosynthetically active radiation [PAR] + UV radiation A [UVA] + UV radiation B [UVB], 280-700 urn; PAR + UVA, 320-700 nm; and PAR, 400-700 nm) under static or simulated-mixing conditions. Under the static condition, UVA and UVB significantly reduced the carbon fixation with the maximum of 22.4 and 15.3%, respectively; while lower UVR-related photosynthetic inhibition was observed in case of phytoplankton samples being subjected to mixing. At a moderate level of mixing (i.e., circulation time 80 min), the UVA and UVB caused inhibition were lowered by 52.1 and 79.6%, respectively. Based on this it could be stated that vertical mixing induced by winds and/or tides in the natural environments could reduce the inhibitory effect of solar UVR on phytoplankton productivity in the coral reefs water.